THE EFFECT OF CAPITAL EXPENDITURE, INVESTMENT, AND GENERAL ALLOCATION FUNDS ON THE RATE OF ECONOMIC GROWTH IN REGENCIES AND CITIES IN RIAU PROVINCE, 2016-2020 - Devia Agustia; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This study aims to test and analyze the effect of capital expenditure, investment, and general allocation funds on the rate of economic growth in regencies and cities in Riau Province in 2016-2020. Sampling in the study was carried out by saturated sampling and obtained a sample of 12 regencies and cities in Riau Province using secondary data. This research data uses the panel data regression method and the Pooled Least Square (PLS) estimation model is selected as the best estimator. The data were analyzed using STATA/MP Version 17 software with a significance level of 0.05. The results of this study indicate that the capital expenditure variable has a positive and insignificant effect on economic growth, while the investment and general allocation fund variables have a positive and significant effect on economic growth.